THE OCCURRENCE OF CODE SWITCHING ON PERSONAL MESSAGE OF BLACKBERRY MESSENGER - Tajudin Tajudin (Journal of English and Education, 2013)
The study aims to investigate languages used in code switching on personal message of BlackBerry messenger (PM of BBM), the types of code switching, and the reasons of BBM users in using code switching. This research involved 25 university students in Bandung as samples. The data were gathered through compiling the PM of BBM and distributing questionnaires. Several theories were applied to analyze the data, namely theory of switching types proposed by Poplack(1980), and theory of reasons of switching investigated by Hoffman (1991, in Tiana, 2009), and Savile-Troike (1986). The findings revealed that the users tended to use group of switched-languages (Indonesian-English) in code switching (80%).On the other hand, dealing with types of code switching appeared on PM of BBM, intersentential switching is the most dominant switching type (40.63%). Furthermore, the data analysis result from questionnaires indicated that most of the respondents (24%) stated that they did switching for real lexical need, which is the BBM users mostly used code switching on their PM because lack of equivalent lexicon. Keywords: Code switching, personal message, BlackBerry messenger, types, reasons.